PREVALENCE OF ASYMPTOMATIC BACTERIURIA AND ITS MICROBIOLOGICAL PROFILE IN PREGNANCY AT TERTIARY CARE HOSPITAL, JABALPUR - PATIDAR, PRAGYA; PATEL, KIRTI; MISHRA, SAKSHI; SINGH, ARCHANA (International Journal of Current Pharmaceutical Research, 2024)
Objective: To determine the prevalence of asymptomatic bacteriuria (ASB), microbiological profile, and pregnancy outcome in asymptomatic pregnant women. Methods: Pregnant women attending outpatient clinic were selected randomly. Urine sample by clean catch method collected and battery of tests were performed. Prevalence of ASB and pregnancy outcome studied. Results: Total 114 pregnant women were studied, out of which 6 cases were positive for urine culture. Prevalence rate in our study found to be 5.3%. Study depicted that 33.4% women with asymptomatic bacteriuria had premature rupture of membranes, 16.7 % women had pre-eclampsia and 16.7% had severe anemia. 50 % babies were premature, 33.4% had fetal growth restriction and 16.7% developed acute respiratory distress syndrome. Conclusion: Urinary tract infections are common during pregnancy. Asymptomatic bacteriuria can progress to pyelonephritis and may result in adverse pregnancy outcome. Prevalence rate found to be 5.3%. Premature rupture of membranes and premature births were major adverse pregnancy outcome. E. coli was most common bacterial isolate found in the study and was highly sensitive to cefuroxime sodium. Pregnancy complications may be avoided by using regular screening with urine cultures.